Collaborative language learning and teaching (Cambridge University Press, 1992)
The aim of this book is to present, in an accessible manner, current theory and resources relating to cooperative learning. Collaborated research team teaching, experiential learning, teacher research, learner-centered classrooms, and learning how to learn are some of the topics discussed. The book is written for teachers, learners, educators, and researchers who are interested in experimenting with alternative ways of organizing teaching and learning, or who are concerned with promoting a philosophy of cooperation, and who wish to create an environment in which teachers, learners and researchers can work together and learn from one another